Feeding ecology and nursery of marine larval fishes - Ara, Roushon; Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Abd. Ghaffar, Mazlan; Rahman, Md. Aminur (Academic Journals, 2013)
Larval stage of marine fishes, habitat characteristics, nursery and feeding ecology has been discussed in this review. Identification of fish larvae is difficult and that is why limited research is available on biology of fish larvae in the Indo-Pacific coastal region. Estuaries play a vital role in energy transfer between a river and a sea, which is especially important for many commercial coastal fishes whose larvae and juveniles are dependent on the estuary as a nursery and feeding grounds. Many coral reef fish species use mangrove and seagrass beds as nursery habitats. Diet composition of the family Clupeidae were made up of seven major categories to include phytoplankton, plant-like matter, debris, fragment of copepod, algae and unidentified food items. The most predominant food item in the gut of clupeids was phytoplankton (82.53%).